The effect of catalytic copper pretreatments on CVD graphene growth at different stages. (8th December 2020) - Li, Na; Zhang, Ru-Jing; Zhen, Zhen; Xu, Zhen-Hua; Mu, Ren-De; He, Li-Min
Abstract: The controllable synthesis of high-quality and large-area graphene by chemical vapor deposition (CVD) remains a challenge nowadays. The massive grain boundaries in graphene grown on polycrystalline Cu by CVD significantly reduce its carrier mobility, limiting its application in high-performance electronic devices. Here, we confirm that the synergetic pretreatment of Cu with electropolishing and surface oxidation is a more efficient way to further suppress the graphene nucleation density (GND) and to accelerate the growth rate of the graphene domain by CVD. With increasing the growth time, we found that the increasing amount of GND and growth rate of the graphene domain were both decreasing during the whole CVD process when the Cu surface was not oxidized. By contrast, they kept growing over time when the Cu surface was pre-oxidized, which suggested that the change trends of the effects on the GND and growth rate between the Cu surface morphology and oxygen were opposite in the CVD process. In addition, not only the domain shape, but the number of graphene domain layers were impacted as well, and a large number of irregular ellipse graphene wafers with dendritic multilayer emerged when the Cu surface was oxidized.